2019
DOI: 10.1177/1179069519856876
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neurogenesis and the Promise of Adult Neural Stem Cells

Abstract: The adult brain, even though largely postmitotic, is now known to have dividing cells that can make both glia and neurons. Of these, the precursor cells that have the potential to make new neurons in the adult brain have attracted great attention from researchers, anticipating their therapeutic potential for neurodegenerative conditions. In this review, I will focus on adult neurogenesis, from the perspective of the overall neurogenic potential in the adult brain, current understanding of the ‘adult neural ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 91 publications
(125 reference statements)
0
38
0
Order By: Relevance
“…The dentate gyrus (DG) of the hippocampus, is a packed V-shaped layer of granule neurons involved in spatial memory formation and pattern separation 12 , which hosts a niche of radial glia-like cells supporting adult neurogenesis 13 . During embryonic development, DG granule neuron progenitors originate from the dentate neuroepithelium (DNE) or primary (1ry) matrix of the archicortex.…”
Section: Introductionmentioning
confidence: 99%
“…The dentate gyrus (DG) of the hippocampus, is a packed V-shaped layer of granule neurons involved in spatial memory formation and pattern separation 12 , which hosts a niche of radial glia-like cells supporting adult neurogenesis 13 . During embryonic development, DG granule neuron progenitors originate from the dentate neuroepithelium (DNE) or primary (1ry) matrix of the archicortex.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and molecular mechanisms that guide the progression from a dividing NSC to a functional neuron are not fully understood. In the mammalian brain, neurogenesis is tightly regulated via both extrinsic environmental influences and intrinsic genetic factors [76,77,78]. Endogenous extrinsic factors include cell-to-cell interactions, niche-derived morphogens, growth factors and cytokines [79,80].…”
Section: Resultsmentioning
confidence: 99%
“…DCX is reported to be strongly expressed by migrating immature neurons ( Kaindl et al, 2006 ; Klempin et al, 2011 ; Madhyastha et al, 2013 ) and in our study, mainly after the multi-hit exposure, DCX expression was upregulated, suggesting an increase in migration of newly generated neurons. Some studies have reported the difference in extent of neurogenesis between sub ventricular (SVZ) and sub granular (SGZ) zone, stating that SVZ regions contain more neural stem cells and with additional amplifying signals, the extent of neurogenesis in SVZ is somewhat higher than SGZ region ( Zhu et al, 2014 ; Ghosh, 2019 ). However, some studies have also reported a decrease in DCX-positive cells in the hippocampus of rats with chronic stress exposure ( Dagytė et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%